LO78: Ready for launch? A survey of readiness factors among 2019 Competence By Design launch disciplines. (May 2020) - Cheung, W.; Hall, A.; Dalseg, T.; Oswald, A.; Cook, L.; Melle, E. Van; Frank, J.
Abstract : Introduction: A critical component for successful implementation of any innovation is an organization's readiness for change. Competence by Design (CBD) is the Royal College's major change initiative to reform the training of medical specialists in Canada. The purpose of this study was to measure readiness to implement CBD among the 2019 launch disciplines. Methods: An online survey was distributed to program directors of the 2019 CBD launch disciplines one month prior to implementation. Questions were developed based on the R = MC2 framework for organizational readiness. They addressed program motivation to implement CBD, general capacity for change, and innovation-specific capacity. Questions related to motivation and general capacity were scored using a 5-point scale of agreement. Innovation-specific capacity was measured by asking participants whether they had completed 33 key pre-implementation tasks (yes/no) in preparation for CBD. Bivariate correlations were conducted to examine the relationship between motivation, general capacity and innovation specific capacity. Results: Survey response rate was 42% (n = 79). A positive correlation was found between all three domains of readiness (motivation and general capacity, r = 0.73, p < 0.01; motivation and innovation specific capacity, r = 0.52, p < 0.01; general capacity and innovation specific capacity, r = 0.47, p < 0.01). Most respondents agreed that successful launch of CBD was a priority (74%). Fewer felt that CBD was a move in the right direction (58%) and that implementation was a manageable change (53%). While most programs indicated that their leadership (94%) and faculty and residents (87%) were supportive of change, 42% did not have experience implementing large-scale innovation and 43% indicated concerns about adequate support staff. Programs had completed an average of 72% of pre-implementation tasks. No difference was found between disciplines (p = 0.11). Activities related to curriculum mapping, competence committees and programmatic assessment had been completed by >90% of programs, while <50% of programs had engaged off-service rotations. Conclusion: Measuring readiness for change aids in the identification of factors that promote or inhibit successful implementation. These results highlight several areas where programs struggle in preparation for CBD launch. Emergency medicine training programs can use this data to target additional implementation support and ongoing faculty development initiatives.